1994
DOI: 10.1136/jnnp.57.11.1433
|View full text |Cite
|
Sign up to set email alerts
|

Anterior spinal hernia: an increasingly recognised cause of thoracic cord dysfunction.

Abstract: Two cases of anterior spinal hernia are presented. The medical literature is reviewed, the syndrome characterised, and its cause and treatment discussed. The patient is typically middle aged with a history of stepwise slowly progressive mid-thoracic anterior hemicord syndrome manifesting as hemianalgesia below the affected segment, followed by contralateral lower limb spasticity that develops into an asymmetric paraparesis with sparing of dorsal column sensation. Radiological investigation demonstrates an enla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 3 publications
0
29
1
4
Order By: Relevance
“…In all cases the spinal cord was displaced anteriorly. Similarly, there was focal cord atrophy in 14-15 of 16 cases [1] (in 1 case there was disagreement about the presence of cord atrophy). T 2 hyperintensity within the affected cord was a common feature, present in 10 of 16 cases.…”
Section: Radiological Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…In all cases the spinal cord was displaced anteriorly. Similarly, there was focal cord atrophy in 14-15 of 16 cases [1] (in 1 case there was disagreement about the presence of cord atrophy). T 2 hyperintensity within the affected cord was a common feature, present in 10 of 16 cases.…”
Section: Radiological Findingsmentioning
confidence: 95%
“…The cord prolapses through an anterior or anterolateral dural defect, resulting in a progressive, frequently asymmetrical, thoracic myelopathy. Patients typically present in middle age with slowly progressive neurological dysfunction relating to anterior hemicord dysfunction [1,2]. The condition was described in 1973 by Cobb et al [3], with the first idiopathic case suggested by Wortzman et al [4] a year later; a number of case reports and small series have been published since.…”
mentioning
confidence: 99%
“…Najjar et al [19] proposed that an inflammation might lead to arachnoid adhesion formation and erosion through the dura forming an idiopathic dural defect and subsequent spinal cord herniation. The inflammation resulting from incarceration of the cord [20] may also cause the increased thickness of dorsal arachnoid [17,21,22]. In addition, within several mechanisms suggested as cause of nervous system involvement in AS, inflammation and compression are the main causative mechanisms [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Theories about this congenital defect include a preexisting ventral pseudomeningocele, a meningeal diverticulum, or an extradural arachnoid cyst. 47 Both Wortzman et al 48 and Masuzawa et al 24 suggested that herniation results from a congenital ventral meningocele. No other congenital bony spinal or neural deformities were reported in these cases.…”
Section: Pathogenesismentioning
confidence: 99%
“…47 This vascular mechanism may also explain the lack of improvement in some patients following untethering of the spinal cord.…”
Section: Pathophysiological Features Of Tetheringmentioning
confidence: 99%